Project planning and management for ecological restoration - Rieger, John (The Science and Practice of Ecological Restoration, 2014)
Concern over climate change and the ongoing challenges of managing natural lands have made the field of ecological restoration a growing focus in the agendas of national and international conservation organizations, including the United Nations. The problems facing us are both complex and urgent-and effective solutions are vital. Project Planning and Management for Ecological Restoration presents principles of sound planning and management that will greatly increase the likelihood that projects will be successful. John Rieger, John Stanley, and Ray Traynor have been involved in restoration activities for nearly thirty years, inventing and adapting techniques as well as developing and applying methods as they broke ground for this new field. Rieger and Stanley were part of the small group who, recognizing the need for a professional organization, helped to found the Society for Ecological Restoration in 1987. This book comes out of their experience of doing restoration, through trial and error, setting goals and methodology, and learning what works. The authors focus on process, planning, design, implementation, and management rather than science. They describe a simple project management plan, identify the design approaches and the commitments that decisions require, and explain how design theory is translated to on-the-ground project design. The book includes numerous illustrations, as well as a series of checklists and tables to help restorationists recognize and then correct problems that may arise. The goal of Project Planning and Management for Ecological Restoration is to provide a straightforward framework for developing and executing an ecological restoration project that has the highest potential of being successful. Professionals and practitioners can apply the guidelines offered by the authors to the wide variety of situations and locations where restoration is happening. Long overdue, this book will inform and advance the effective practice of this promising field.